Efflorescence Phenomenon on Concrete Structures - Norsuzailina, Mohamed Sutan; Sinin, Hamdan (Trans Tech Publications, 2013)
Since the introduction of modern pigmented concrete products in the early 1950’s, coloured concrete products have opened new possibilities in the field of building and landscape design and ironically to a new visible phenomenon called efflorescence. Unfortunately, despite careful selection of raw materials and conscientious compliance with the production parameters, colour changes of the finished products are always the enemy. In many cases, these colour irregularities often described as fading is attributed to calcium carbonate efflorescence. One might question how efflorescence can still occurs after presumably, manufacturers have done everything right such as utilized quality materials, had a good mix design, exceeded strength requirements and met production schedule. By studying in depth the mechanism of efflorescence one might answer this mind-boggling question. Although, a great deal of work has been done in investigating the phenomenon of efflorescence and agreement has been reached to a large extent by researchers worldwide on the mechanism behind the formation of efflorescence, there is still no effective methods that can be used by concrete manufacturers to prevent the formation of efflorescence on finished concrete products. This paper has the purpose of providing some direction for future work to mitigate this phenomenon.